As macro e micro instituições no sistema agroindustrial da piscicultura - Franco, Jheine Oliveira Bessa (2014)
Pisciculture is considered a sustainable activity that ensures food security. In Brazil, this activity still has some impediments that may influence its development in the country such as some issues with limited access due to technical and economical regulations. Apart from these problems, the performance and efficiency of the agents that compose this sector are interfered with determinations originated in an institutional environment that set the economic environment, particularly in the production segment. This study aimed to understand the influence of macro and micro institutions in these relations, involving agents of the segments of production and processor in SAG freshwater fish farming in Paraná. As theoretical contribution, theories of New Institutional Economics (NIE), mainly North (1991) focused on macro institution were used, Transaction Cost Economics (TCE) Williamson (1985) Measurement Cost Theory (MCT) Barzel (2005), the last ones cited, contributed to the understanding of the micro institutions. The study focused on the realization of a descriptive qualitative study, with a sectional and longitudinal perspective, which used as a tool for primary data collection, semi-structured interview with the producers and processors of fish farming SAG Paraná. Regarding the secondary data, those were obtained from government departments, institutions and governmental organs related to fishing activity. For data analysis, was used the method of content analysis. The survey results showed that macro institutional environment from this sector is still being established; being so the concern of the producers and processors involves the granting of environmental licenses. In addition, for those agents, the rules about the macro institutional environment and procedures established by those laws are complex, bureaucratic and time consuming, generating some uncertainties. Thus, certain rules, formal or not, are stipulated by the processors to be obeyed by producers seeking to decrease these uncertainties and make possible the development of the activity. When considering the assumptions of TCE and MCT, it is observed that even with uncertainty, asset specificity and the possibility of opportunistic behavior, the measurement is easily verified. With such characteristics, the relationship between producers and processors can take place through various forms of governance, being those predominantly hybrid. These forms range from the nearest from the market , mainly involving trust and reputation as a way of warranty , even the most formal, with the presence of the integration contract , besides the presence of some vertically integrated producers . However , it was observed that in cases of more formalized hybrid relations, there is the occurrence of asymmetric information on the part of producers and may lead to loss of property rights and opening the possibility of opportunism by the processors . Thus, only the contract demonstrates unsatisfactory because it is incomplete, and insufficient to solve disputes by legal means. This fact leads to the need for further negotiations and agreements, as well as margins contracted not to distinguish the legal right and the economic right, confirming the possibility of appropriation of income by the processors. In this regard it is noted that the relationship between producers and processors of fish agents SAG, studied in the state of Paraná, only formal institutions (judicial mechanisms) do not guarantee the efficiency of the exchange process between the agents, being complemented by informal institutions that contribute to the trust and reputation among them.